SYSTEMATIC REVIEW ON THE INFLUENCE OF GREEN HRM PRACTICES, SUSTAINABLE WORK CULTURE, AND CORPORATE SOCIAL RESPONSIBILITY ON EMPLOYEE ENGAGEMENT THROUGH ORGANIZATIONAL COMMITMENT - Achmad Nuril Huda; Budi Eko Soetjipto; Ludi Wisnu Wardhana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
In organizations that prioritize sustainability, employee engagement serves as a strategic element in generating value and fostering customer loyalty. This study systematically examines the influence of Green Human Resource Management (GHRM), sustainable work culture, and Corporate Social Responsibility (CSR) on employee engagement, with organizational commitment (OC) acting as a mediating variable. A Systematic Literature Review (SLR) was manually conducted on 76 Scopus-indexed articles published between 2019 and 2025, employing Boolean operators and keyword mapping techniques. The findings reveal that GHRM influences engagement through green empowerment and green training; work culture exerts its influence through values, ethics, and spirituality; while CSR contributes through meaningful work and trust. Organizational commitment functions as a key mediator that links these three elements to employee engagement, which in turn impacts employee involvement. The integrative conceptual model, grounded in Social Exchange Theory, the AMO Framework, and Stakeholder Theory, connects sustainability strategies with customer loyalty. This study contributes to the advancement of cross-disciplinary frameworks and offers practical recommendations for value-based human resource and marketing management.